Disaster management: a study of the Regional Disaster Management Agency of Buton District - Sa'ban, L.M. Azhar; Maulana Wijaya, Andy Arya; Ode Bau, Waode Asmawati (Geuthèë Institute, Aceh, 2025)
Although disasters cannot be prevented, their impacts can be predicted or reduced. Considering the large potential for disasters that occur in Buton Regency, disaster prevention initiatives are very important to increase preparedness to face various types of disaster risks that may and will occur at any time. Knowing the management of the Buton Regency Regional Disaster Management Agency in dealing with disasters is one of the study objectives to be achieved. This research uses qualitative methodology. BPBD Buton Regency in implementing disaster prevention management consists of mitigation, preparedness, responsiveness and recovery stages. The mitigation stage carried out by the Buton Regency BPBD began with conducting outreach to people living in disaster-prone areas, making maps of disaster-prone areas and conducting outreach and training to the community. Preparedness carried out by BPBD Buton Regency provides information about community readiness to respond to disasters, community preparedness when facing disasters such as building emergency tents, public kitchens, and evacuating disaster victims. Buton Regency BPBD's response or responsiveness provides public complaint services regarding disaster incident reports via WhatsApp. The recovery carried out by BPBD Buton Regency is to restore the condition of the community and environment affected by the disaster by repairing and restoring all aspects with the target of normalizing people's lives in the disaster-affected area.